The Influence of Traditional Games on the Development of Preschool - Cinthia Rani Saputri; Zolla Amely Ilda; Idrawati Bahar; Tisnawati; Elvia Metti (Journal of Applied Holistic Nursing Science, 2026)
Preschool-aged children are in the pre-operational stage, where they begin to demonstrate symbolic thinking skills, namely the ability to use symbols, images, or words to represent objects and events in their environment. Children are able to use language to express ideas and feelings, although their thinking patterns are still egocentric and they are not yet able to see other people's perspectives. Delays in development during this period can impact subsequent stages of development, particularly when children enter school age, which requires cognitive, social, and emotional readiness. This study aims to assess the influence of traditional games on the development of preschool-aged children at TK Pertiwi 1 Kantor Gubernur of Padang City. basic procedures, research design, selection and size of study subjects; observational and analytical methods Data collection was conducted using the Pre-Screening Development Questionnaire (KPSP). The statistical test used was the Wilcoxon test. The results showed that the average development of children before playing traditional games was 5.37 and after playing traditional games was 8.51. There was a significant effect on the development of preschool-aged children before and after being given traditional games, with a mean difference of 3.14 and a p-value of 0.000. The recommendation of this study is that nurses should monitor the development of preschool-aged children and provide stimulation by implementing traditional games such as “Long Snake and How Many ABCs.